Synthesis of FeOOH and FeOOH@ZnO by hydrothermal method and the adsorption of S2- in wastewater - Ge, Baocai; Li, Fen; Meng, Fanzhu; Yang, Ying; Yu, Cailian (Journal of Environmental Engineering and Landscape Management, 2022)
FeOOH and FeOOH@ZnO were prepared by hydrothermal synthesis, and their structures and adsorption properties toward S2− were studied. The results showed that too high hydrothermal temperature was not conducive to the adsorption of S2−. However, using sodium dodecyl sulfate (SDS) for FeOOH preparation and adding nanometer ZnO (FeOOH@ZnO) could significantly improve the adsorption of S2− by FeOOH, and adsorption removal rate was close to 90.0% and adsorption amount was 87.5 mg·g−1. The structural analysis showed that the modification of FeOOH by SDS and the addition of nano-ZnO resulted in the reduction in size of the FeOOH particles, forming amorphous inclusion structure with ZnO present inside and FeOOH outside. The specific surface area of FeOOH@ZnO was found to be higher than that of FeOOH. Therefore, it is beneficial to the adsorption of S2−. XPS fitting results showed that ferrous deposits appeared in the process of adsorption of S2− by FeOOH@ZnO, and it was considered that the oxygen of Fe = O was replaced with sulfur.